Enhancement of wheat grains antioxidant activity by solid state fermentation with Grifola spp. - Postemsky, Pablo Daniel (2014)
Grifola frondosa, Grifola gargal, and Grifola sordulenta are edible and medicinal mushrooms with antioxidant properties. To obtain wheat flour (Wf ) with a higher antioxidant activity than the one exhibited by regular Wf, solid state fermentation (SSF) of wheat grains with mycelia of those Grifola spp. was used to obtain biotransformed wheat grain (BWG) flour. The methanolic extract of control Wf and BWG flour of G. gargal, G. sordulenta, and G. frondosa (Gf WG, GgWG, and GsWG, respectively) were studied for their radical scavenging (RS) activity against 2,2-diphenyl-1-picrylhydracyl (DPPH) and their Fe(III) reducing power (RP). The values for RS-EC50 decreased in BWG flour, therefore presenting a higher antioxidant activity: GgWG (0.56 mg/mL), Gf WG (0.81 mg/mL), and GsWG (5.80 mg/mL) in comparison to Wf (57.60 mg/ mL). The antioxidant content for this RS activity in terms of ascorbic acid content (RS-EQAA) was highest in Gf WG, followed by GgWG and GsWG (71.73, 14.46, and 3.02 mg/g, respectively) and lowest in Wf (0.25 mg/g). The RP-EC50 values in GgWG, Gf WG, and GsWG were low (0.55, 0.64, and 4.20 mg/mL, respectively) with respect to Wf (55.00 mg/mL). Compared with Wf (0.56 mg/g), the RP capacity in terms of ascorbic acid content (RP-EQAA) was very high in Gf WG (193.67 mg/g) followed by GgWG and GsWG (31.42 and 8.74 mg/g, respectively). The high content in gallic acid equivalents was consistent with RS-EQAA and RP-EQAA contents. TLC revealed that antioxidant activity in BWG could be related to the presence of phenolic compounds. Thus, a valuable food alternative can easily be obtained with wheat grains, that is, by markedly increasing their antioxidant value through SSF with Grifola spp.